NIR‐Assisted MgO‐Based Polydopamine Nanoparticles for Targeted Treatment of Parkinson's Disease through the Blood–Brain Barrier. Issue 23 (13th October 2022) - Gao, Yifei; Cheng, Yuxue; Chen, Jiapeng; Lin, Danmin; Liu, Chao; Zhang, Ling‐Kun; Yin, Liang; Yang, Runcai; Guan, Yan‐Qing
Abstract: The blood–brain barrier (BBB) is a major limiting factor that prevents the treatment of Parkinson's disease (PD). In the present study, MgOp@PPLP nanoparticles are explored by using MgO nanoparticles as a substrate, polydopamine as a shell, wrapping anti‐SNCA plasmid inside, and modifying polyethylene glycol, lactoferrin, and puerarin on the surface to improve the hydrophilicity, brain targeting and antioxidant properties of the particles, respectively. MgOp@PPLP exhibits superior near‐infrared radiation (NIR) response. Under the guidance of photothermal effect, these MgOp@PPLP particles are capable of penetrating the BBB and be taken up by neuronal cells to exert gene therapy and antioxidant therapy. In both in vivo and in vitro models of PD, MgOp@PPLP exhibits good neuroprotective effects. Therefore, combined with noninvasive NIR radiation, MgOp@PPLP nanoplatform with good biocompatibility becomes an ideal material to combat neurodegenerative diseases. Abstract : MgOp@PPLP nanoparticles are explored which exhibit superior near‐infrared radiation response. Under the guidance of photothermal effect, these MgOp@PPLP particles are capable of penetrating the blood–brain barrier and be taken up by neuronal cells to exert gene therapy and antioxidant therapy. In both in vivo and in vitro models of Parkinson's disease, MgOp@PPLP exhibits good neuroprotective effects.